Problems of Learning Arabic for Non-Islamic School Graduate Students at the Arabic Language Education Program at Sultan Thaha Saifuddin State Islamic University Jambi - Dwi Arian Putra Mandaka; Wachida Muhlis; Ibnu Hajar; Khairul Mizan; Rohmatun Luluk Isnaini (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Salatiga, 2023)
This research discusses the problems of learning Arabic for non-Islamic boarding school graduate students in the Arabic Language Education Study Program at the Sultan Thaha Saifuddin Jambi State Islamic University (UIN Sulthan Thaha Saifuddin Jambi). This research aims to explain and describe the problems faced when learning Arabic for UIN Sulthan Thaha Saifuddin Jambi students who are non-Islamic boarding school graduates. The method used in this research is a descriptive qualitative method with a case study approach. The data collection technique uses observation, interviews, and documentation techniques. This research aims to find the right solution to deal with the problems found so that it can have a positive impact on non-Islamic boarding school students in learning Arabic. The results of this research show that in the process of learning Arabic at UIN Sulthan Thaha Saifuddin Jambi, there are several problems, including linguistic problems, such as problems of phonetics, morphology, and structure, as well as problems of a non-linguistic nature such as learning motivation, learning facilities, teaching methods, learning time, and learning environment.